Feasibility of injectable Depot medroxyprogesterone acetate in a semi urban camp setting - Nautiyal, Ruchira; Bijalwan, Rajeev; Maithili, B.; Sinha, Latika N. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: The contraceptive method mix in India has been dominated by female sterilization for a long time. Initiatives have been taken to make Depot medroxyprogesterone acetate (DMPA) available through the public sector of the country. Considering the privacy, safety and efficacy of this long acting method, the study was undertaken to evaluate the acceptance of DMPA in field camps amongst semi urban population. Methods: A cross sectional evaluation study was carried out with married women who accepted DMPA from the basket of contraceptives offered to them. Selection was facilitated by adequate counseling. After counseling, the clients were followed up during subsequent doses for a year for the acceptance and side effects. A checklist was filled comprising detailed history and other variables. The data was expressed in number and percentage and statistical analysis was done on SPSS -19. Results: The mean age of 45 eligible women who accepted DMPA was 26.5 years .Fifty one percent of women were primiparous and forty two percent were lactating during the study period. Majority (80%) were self-motivated to receive subsequent injections. There was no pregnancy in DMPA users. The commonest adverse effect was amenorrhea (49%) followed by irregular spotting (32%) and menorrhagia (14%). Fourteen subjects discontinued DMPA after one or two injections but 58.5% acceptors considered this a good method for birth spacing and wanted to continue it for a longer period. Conclusions: DMPA remains a valid, safe and confidential but neglected contraceptive in India. There is a need to create an awareness program for common people and also to build a supportive environment for users at all levels.